1994
DOI: 10.1149/1.2055007
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐Dependent Methanol Electro‐Oxidation on Well‐Characterized Pt‐Ru Alloys

Abstract: The kinetics of methanol electro‐oxidation on well‐characterized Pt‐Ru alloy surfaces were measured in sulfuric acid solution as a function of temperature. The alloy surfaces were prepared in ultrahigh vacuum with the surface composition determined by low energy ion scattering. It was found that the activity of Ru towards the dissociative adsorption of methanol is a strong function of temperature. This change in the adsorptive nature of the Ru sites with temperature produced a variation in the optimum surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

46
402
2
13

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 595 publications
(463 citation statements)
references
References 7 publications
46
402
2
13
Order By: Relevance
“…As the temperature is increased, the ability of Ru sites to adsorb and decompose methanol improves, which results in improved performance for higher-Ru-content electrodes. 57 The current efficiencies plotted in Figure 7B also depict a change in behavior at higher temperatures. At 25°C, the Pt 100 Ru 0 electrode exhibited the greatest conversion of methanol to carbon dioxide at over 90%.…”
Section: Resultsmentioning
confidence: 91%
“…As the temperature is increased, the ability of Ru sites to adsorb and decompose methanol improves, which results in improved performance for higher-Ru-content electrodes. 57 The current efficiencies plotted in Figure 7B also depict a change in behavior at higher temperatures. At 25°C, the Pt 100 Ru 0 electrode exhibited the greatest conversion of methanol to carbon dioxide at over 90%.…”
Section: Resultsmentioning
confidence: 91%
“…Os eletrocatalisadores PtRh/C com razões atômica Pt:Rh 90:10 e 50:50 apresentam quatro picos de difração em aproximadamente 2θ = 40 o , 47 o , 67 o e 82 o os quais são associados aos planos (111), (200), (220) e (311), respectivamente, da estrutura cúbica de face centrada (CFC) de platina e ligas de platina [20]. Os cálculos do parâmetro de rede [21] [24]. Para os cál-culos do tamanho médio de cristalito utilizando a equação de Scherrer (Tabela 1) foram selecionados os picos de difração correspondente ao plano (220) dos diferentes eletrocatalisadores.…”
Section: Resultsunclassified
“…e velocidade de varredura de 2°min -1 . O tamanho médio de cristalito foi estimado através dos difratogramas de raios X utilizando a equação de Scherrer [21].…”
Section: Procedimento Experimentalunclassified
“…The activity of Ru for the methanol adsorption appears to be strongly temperature dependent. In a recent article Gasteiger et al [13] showed that at 60°C the optimum Ru composition is about 30%.…”
Section: Introductionmentioning
confidence: 99%